2014
DOI: 10.1002/ppul.22908
|View full text |Cite
|
Sign up to set email alerts
|

An atypical presentation of pulmonary air‐leak syndrome and multisystem toxic epidermal necrolysis

Abstract: Toxic epidermal necrolysis (TEN) is a rare and potentially fatal mucocutaneous condition that may affect both children and adults. TEN mortality rates vary greatly between both patient populations, but multisystem involvement is common. Management presents many challenges as there is no specific therapy for TEN, and patients often require the expertise of burn units. We report a child who survived TEN with multisystem involvement including the rare but life threatening occurrence of a pulmonary air-leak syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Mediastinal emphysema and pneumothorax in patients with SJS/TEN are rare, and their pathogenesis with SJS/TEN has been proposed to result from airway obstruction caused by detached airway mucosa, air trapping caused by coughing, and destruction of alveoli 14. In the present case, mediastinal and subcutaneous emphysema developed several days after admission, with no findings of pulmonary air leakage on presentation.…”
Section: Discussionmentioning
confidence: 51%
“…Mediastinal emphysema and pneumothorax in patients with SJS/TEN are rare, and their pathogenesis with SJS/TEN has been proposed to result from airway obstruction caused by detached airway mucosa, air trapping caused by coughing, and destruction of alveoli 14. In the present case, mediastinal and subcutaneous emphysema developed several days after admission, with no findings of pulmonary air leakage on presentation.…”
Section: Discussionmentioning
confidence: 51%
“…A retrospective study of 32 SJS/TEN cases found 50% to have abnormal lung function tests during routine follow-up (61). In the published literature, RS involvement following SJS/TEN has been characterized by chronic lung disease, bronchiolitis obliterans, interstitial lung disease, pulmonary air leak syndrome, laryngeal obstruction, and obliterative bronchitis, among others (57,(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76). The genitourinary system is also not spared in SJS/TEN.…”
Section: Internal Organ Involvement As An Additional Marker Of Steven...mentioning
confidence: 99%
“…These air-leak syndromes are postulated to occur in the setting of alveolar rupture that results from air trapping due to the obstruction of airways by mucosal debris. Such complications are more frequently seen in pediatric patients, [37][38][39] possibly due to the occlusive effect on smaller airways.…”
Section: Acute Respiratory Complicationsmentioning
confidence: 99%